Atherosclerosis in geriatric patients known to be healthy - Genç, Ahmed Bilal; Yaylaci, Selcuk; Acıkgöz, Seyyid Bilal; Yildirim, Mehmet; Aksoy, Yakup Ersel; Vatan, Mehmet Bülent; Dheir, Hamad; Sipahi, Savas (International Journal of Research in Medical Sciences, 2019)
Background: The aim of the present study is to determine the presence of atherosclerosis in geriatric patients who are known to be healthy and examine sociodemographic and laboratory parameters affecting the presence of atherosclerosis. Method: 90 healthy volunteers including 66(73.3%) non-geriatric ones and 24(26.7%) geriatric ones were included in the study. It was analyzed whether there was a correlation between the two groups in terms of the parameters of gender, age average, alcohol consumption, smoking, carotid intima-media thickness (CA-IMT), and pulse wave velocity (PWV). Sociodemographic and laboratory parameters of the volunteers with and without atherosclerosis in the geriatric group were examined. Results: Among geriatric volunteers (Group 1), 13(54.2%) were male; whereas, among non-geriatric volunteers (Group 2), 41(62.1%) were male. CA-IMT was determined to be higher in Group 1 (averagely 0.80±0.12 mm) than Group 2 (averagely 0.62±0.14 mm) (p:<0.001). PWV was significantly higher in Group 1 (averagely 10.32±1.44 m/s) than Group 2 (6.26±1.09 m/s) (p:<0.001). After PWV or CA-IMT examination, atherosclerosis findings were determined in 12 healthy geriatric volunteers (50%) in Group 1. Conclusion: It should be remembered that even though atherosclerosis can be frequently observed in geriatric individuals who are known to be healthy, it may also go unnoticed. Determination of atherosclerosis with noninvasive methods will be helpful in preventing complications that might be caused by atherosclerosis.